2021
DOI: 10.1002/cpe.6707
|View full text |Cite
|
Sign up to set email alerts
|

An efficient approach for detecting anomalous events in real‐time weather datasets

Abstract: Event detection in real‐time is applied in diverse domains such as detection of fraudulent activities in commercial transactions, detection of faulty systems in industries, and so forth. Businesses and organizations benefit from the actionable information obtained through various techniques available for anomalous event detection. Real‐time event detection is nowadays handled through streaming data frameworks. Traditional approaches effectively handle event detection in real‐time but with more false positives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Data were collected from the urban traffic network of Hague, and the results were compared to those resulting from naïve multivariate long short-term memory in terms of running time. Arora et al [41] suggested a framework to detect global outliers consisting of five stages, namely data collection, data pre-processing, data splitting, optimization and training models, and model evaluation using deep learning, including long short-term memory and a recurrent neural network for the offline mode and deep neural networks for the online mode. PubNub sensor datasets were used for the evaluation, wherein the offline mode was compared among different models and weather sensor data were used to evaluate the online model.…”
Section: Deep Learningmentioning
confidence: 99%
“…Data were collected from the urban traffic network of Hague, and the results were compared to those resulting from naïve multivariate long short-term memory in terms of running time. Arora et al [41] suggested a framework to detect global outliers consisting of five stages, namely data collection, data pre-processing, data splitting, optimization and training models, and model evaluation using deep learning, including long short-term memory and a recurrent neural network for the offline mode and deep neural networks for the online mode. PubNub sensor datasets were used for the evaluation, wherein the offline mode was compared among different models and weather sensor data were used to evaluate the online model.…”
Section: Deep Learningmentioning
confidence: 99%
“…Event schema induction is an essential step in understanding events to adapt to new domains, and it is widely used in various event tasks, such as event detection, 1 event extraction, 1,2 and causal inference 3 . Previous studies rely on manually predefined event schema and corresponding annotations to learn their model.…”
Section: Introductionmentioning
confidence: 99%